Nasal high flow oxygen therapy in hospitalised neonatal foals. (13th October 2021) - Floyd, Emily; Danks, Sophie; Comyn, Imogen; Mackenzie, Catriona; Marr, Celia M.
Abstract: Background: Respiratory disease is common in critically ill neonatal foals. Traditional oxygen therapy (TOT) with nasal insufflation of oxygen is often used to provide first‐line respiratory support. Mechanical ventilation is used in foals which require a greater level of support but requires specialist expertise and can be associated with significant complications. Non‐invasive ventilation (NIV) enables a greater level of respiratory support without the need for intubation. High flow oxygen therapy (HFOT) is a mode of NIV commonly used in human intensive care. Objectives: To describe the use of HFOT in hospitalised neonatal foals. Study design: Retrospective case series. Methods: Hospital records of neonatal foals admitted between 2018 and 2019 that received treatment with HFOT were reviewed. Clinical data and complications were recorded. Results: Fourteen foals were identified and the median duration of use was 43 hours (range 2‐93 hours) with a median flow rate of 0.7L/kg/min (range 0.42‐1.67). Ten foals survived to discharge. No significant complications associated with the technique were recorded. Main limitations: A small study population which was retrospectively reviewed. Conclusions: This study provides preliminary information about the clinical use of HFOT in neonatal foals. The technique was well tolerated and no significant adverse effects were noted. However, further study is required to evaluate efficacy.